B-Cell Receptor-Associated Protein 31 Promotes Metastasis via AKT/β-Catenin/Snail Pathway in Hepatocellular Carcinoma - Liu, Tengfei; Yu, Junming; Ge, Chao; Zhao, Fangyu; Miao, Chunxiao; Jin, Wenjiao; Su, Yang; Geng, Qin; Chen, Taoyang; Xie, Haiyang; Cui, Ying; Yao, Ming; et al. (Frontiers in Molecular Biosciences, 2021)
Hepatocellular carcinoma (HCC) is one of the most lethal tumors worldwide, characterized with high heterogeneity and inclination to metastasize. Emerging evidence suggests that BAP31 gets involved in cancer progression with different kinds. It still remains unknown whether and how BAP31 plays a role in HCC metastasis. Epithelial–mesenchymal transition (EMT) has been a common feature in tumor microenvironment, whose inducer TGF-β increased BAP31 expression in this research. Elevated expression of BAP31 was positively correlated with tumor size, vascular invasion and poor prognosis in human HCC. Ectopic expression of BAP31 led to increased metastatic potential while BAP31 knockdown markedly attenuated migration and invasion in HCC cells and mice orthotopic xenografts. BAP31 mediated epithelial–mesenchymal transition (EMT), and enhanced the expression level of EMT-related factors Snail and decreased that of E-cadherin. BAP31 also activated AKT/β-catenin pathway, which mediated its promotional effects on EMT process. AKT inhibitor further counteracted the activated AKT/β-catenin/Snail upon BAP31 overexpression. Moreover, silencing Snail in BAP31-overexpressed cells reversed enhanced migratory and invasive abilities of HCC cells. In HCC tissues, BAP31 expression was positively correlated with Snail. In conclusion, BAP31 promotes HCC metastasis by activating AKT/β-catenin/Snail pathway. Thus, our study implicates BAP31 as potential prognostic biomarkers, and provides valuable information for HCC prognosis and treatment.